Application of the Nanosecond Pulses - Krymsky, V.V. (Радиофизика и радиоастрономия, 2002)
In operation two usages of short impulses are considered: a radiolocation and physical chemistry. The features of the characteristics of units of an impulse locator are reduced. Its high noise immunity is marked. The examples of application of power electromagnetic impulses for an exposure of water, water solutions, foundry mixtures and melts of metals are reduced. The considerable changes of properties of substances after an exposure are marked. Рассматривается использование коротких импульсов в радиолокации и в физической химии. Получены особенности характеристик составных частей импульсного локатора. Отмечена его высокая шумоустойчивость. Приведены примеры применения мощных электромагнитных импульсов для облучения воды, водных растворов, расплавленных смесей и сплавов металлов. Отмечены существенные изменения свойств веществ после облучения. Розглянуто застосування коротких імпульсів у радіолокації та у фізичній хімії. Отримано особливості характеристик складових частин імпульсного локатора Наведено приклади застосування потужних електромагнітних імпульсів для опромінення води, водних розчинів, розплавлених сумішей та сплавів металів. Відзначено суттєві зміни властивостей речовин після опромінення.